Facilities management managing maintenance for buildings and facilities - Levitt, Joel, 1952- ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Momentum Press, 2013)
The facilities management field has evolved in recent years. This evolution has been driven in part by both long-term and cyclical changes in the economy. Other changes to the field have been triggered by fundamental adjustments in the way business is conducted. When the economy goes sour, property development organizations start to look to building management and, in turn, maintenance departments as revenue sources. Maintenance departments bring a project-based world view, which has both advantages and disadvantages.
List of figures -- List of tables -- Introducing the author -- Introduction -- Acknowledgments -- Introduction to facilities management -- The job of the facilities manager -- Building safety -- Building security -- Disaster and disaster recovery -- Lean maintenance for buildings -- Green buildings, LEED, and energy savings -- Legal contracts in facility management -- Contracting -- Building handbook and maintenance manual -- In-house maintenance and building crews -- Purchasing and stocking materials -- Computerization -- Other technology systems -- Budgeting for maintenance of buildings, facilities, and equipment -- Maintenance fitness questionnaire -- Let's get maintenance organized! -- Management of housekeeping -- Preventive maintenance (PM) -- Appendix -- Index.
Includes index.
Also available in print.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF t.p. (viewed on February 22, 2013).
Keywords: Facility management; Facilities management; Building management; Building maintenance; Building maintenance management; Facilities maintenance; Managing building maintenance; Preventive maintenance for buildings; PM system for buildings; PM system for facilities; Facility Manager handbook; Maintenance management for buildings; Building manager; Maintenance management of stadiums; Maintenance of stadiums; Maintenance of office buildings; Maintenance of hospitals; Maintenance of schools; Managing Maintenance of office buildings; Managing Maintenance of hospitals; Managing Maintenance of schools; Electronic books